2018
DOI: 10.1111/ijcp.13065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment outcomes of patients with MRSA bacteremia following antimicrobial stewardship programs with pharmacist intervention

Abstract: AS programs with pharmacist intervention improve mortality in patients with MRSA-B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In this study, we verified whether the ward pharmacists contribute to the active implementation of TDM in anti- MRSA agents using large health insurance claims database. The strength of this study was the provision of more generalized information compared with previous single-center studies [6][7][8][9]. To account for the confounding, we employed the propensity score method for comparison of the proportions of TDM implementation between the ward and non-ward pharmacy services [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we verified whether the ward pharmacists contribute to the active implementation of TDM in anti- MRSA agents using large health insurance claims database. The strength of this study was the provision of more generalized information compared with previous single-center studies [6][7][8][9]. To account for the confounding, we employed the propensity score method for comparison of the proportions of TDM implementation between the ward and non-ward pharmacy services [14].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we verified whether the ward pharmacists contribute to the active implementation of TDM in anti-MRSA agents using large health insurance claims database. The strength of this study was the provision of more generalized information compared with previous single-center studies [ 6 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jokinen and others [27], as well, described that MRSA predicted worse outcomes than did methicillin-susceptible S. aureus. Ohashi et al [28] showed, however, that pharmacists' intervention in MRSA bacteremia improved the survival of sepsis patients. Additionally, Dolin et al [29] described that broad-spectrum antimicrobials would predispose patients to MRSA infection and thus compromise their prognosis.…”
Section: Discussionmentioning
confidence: 99%